Pengaruh Kualitas Produk dan Word of Mouth terhadap Keputusan Pembelian Produk Multivitamin Hemaviton: - Deborah Yessinta Tan; Ugy Soebiantoro (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
Hemaviton is one of the multivitamin and supplement products to maintain stamina and body health produced by PT. Tempo Scan Pacific Tbk which is engaged in trading pharmaceutical products. Researchers conducted this study because of Hemaviton multivitamins which experienced a decline in sales from 2018 to 2020. To determine the effect of product quality on purchasing decisions for Hemaviton multivitamin products at Pradhana Rungkut Medika Clinic Pharmacy, Surabaya. (2) To determine the effect of word of mouth on purchasing decisions of Hemaviton multivitamin products at the Pradhana Pradhana Rungkut Clinic Pharmacy, Surabaya. The population of this research is Multivitamin Consumers at the Medika Clinic Pharmacy Pradhana Rungkut, Surabaya opening 75 respondents. The sampling technique used is a non-probability sampling technique, precisely purposive sampling. The analytical method used is Partial Least Square (PLS). The results showed that: (1) Product Quality variable contributed to purchasing decisions. (2) Word of Mouth contributed to purchasing decisions. Keywords: Product Quality,Word of Mouth,Hemaviton,Purchasing Desicion